A digital health research platform for community engagement, recruitment, and retention of sexual and gender minority adults in a national longitudinal cohort study–—The PRIDE Study. (4th June 2019) - Lunn, Mitchell R; Lubensky, Micah; Hunt, Carolyn; Flentje, Annesa; Capriotti, Matthew R; Sooksaman, Chollada; Harnett, Todd; Currie, Del; Neal, Chris; Obedin-Maliver, Juno
Abstract: Objective: Sexual and gender minority (SGM) people are underrepresented in research. We sought to create a digital research platform to engage, recruit, and retain SGM people in a national, longitudinal, dynamic, cohort study (The PRIDE Study) of SGM health. Materials and Methods: We partnered with design and development firms and engaged SGM community members to build a secure, cloud-based, containerized, microservices-based, feature-rich, research platform. We created PRIDEnet, a national network of individuals and organizations that actively engaged SGM communities in all stages of health research. The PRIDE Study participants were recruited via in-person outreach, communications to PRIDEnet constituents, social media advertising, and word-of-mouth. Participants completed surveys to report demographic as well as physical, mental, and social health data. Results: We built a secure digital research platform with engaging functionality that engaged SGM people and recruited and retained 13 731 diverse individuals in 2 years. A sizeable sample of 3813 gender minority people (32.8% of cohort) were recruited despite representing only approximately 0.6% of the population. Participants engaged with the platform and completed comprehensive annual surveys— including questions about sensitive and stigmatizing topics— to create a data resource and join a cohort for ongoing SGM health research. Discussion: With an appealing digital platform, recruitment and engagement in online-only longitudinal cohort studies are possible. Participant engagement with meaningful, bidirectional relationships creates stakeholders and enables study cocreation. Research about effective tactics to engage, recruit, and maintain active participation from all communities is needed. Conclusion: This digital research platform successfully recruited and engaged diverse SGM participants in The PRIDE Study. A similar approach may be successful in partnership with other underrepresented and vulnerable populations.